The JAK/STAT3 signaling pathway in vaccinia virus infection - Zhou, Yanan (Kansas State University, 2018)
Poxvirus infections continue to threaten human health despite the eradication of smallpox, which was one of the most lethal infectious diseases in human history. Our objectives were to identify the host cell components/functions that are important for poxvirus infection and to gain insights into the molecular mechanism of poxvirus replication, ultimately guiding novel anti-viral development. Using vaccinia virus, the prototype poxvirus, we screened inhibitors of viral replication from over 3,000 chemical compounds, most of which have known cellular targets. This screening revealed numerous JAK/STAT3 inhibitors that could inhibit the replication of vaccinia virus. We further used multiple inhibitors of the JAK/STAT3 pathway and tested their effects on the replication of vaccinia virus in multiple primary and transformed cells through reporter assay and viral infectious particles measurement. The JAK/STAT3 inhibitors being tested were: SC144, an inhibitor of the interleukin 6(IL-6), a receptor of the JAK/STAT3 signaling pathway, AZ960 (a JAK2 inhibitor), Stattic and niclosamide (inhibitors of STAT3). Overall, our data indicate the JAK/STAT3 inhibitors could repressed vaccinia virus replication in multiple cell types, suggesting that the JAK/STAT3 signaling pathway is required for the efficient replication of vaccinia virus. Moreover, we observed that STAT3 was enriched in the cell nucleus, although the phosphorylation level of STAT3 was downregulated in vaccinia virus-infected cells during the early stages of infection. This study demonstrates an important role of the JAK/STAT3 signaling pathway in the replication of vaccinia virus, providing a possible novel direction by which to intervene in poxvirus infection and related diseases.
Keywords: STAT3; Vaccinia virus; Chemical screening